rs10499194 polymorphism in the tumor necrosis factor-α inducible protein 3 (TNFAIP3) gene is associated with type-1 autoimmune hepatitis risk in Chinese Han population. - Enbin Xu; Hailian Cao; Liming Lin; Honglong Liu (PLoS ONE, 2017)
Previous studies have found that the polymorphisms of tumor necrosis factor-α induced protein 3 (TNFAIP3) were associated with several autoimmune diseases. However, the role of TNFAIP3 polymorphisms in type-1 autoimmune hepatitis (AIH-1) remained unclear. The present study aimed to clarify the association of TNFAIP3 polymorphisms with AIH-1 risk in a Chinese Han population. The TaqMan SNP genotyping assay was used to determine the distribution of TNFAIP3 polymorphisms in 432 AIH-1 patients and 500 healthy controls. The association of TNFAIP3 polymorphisms and clinical characteristic was further evaluated. Five TNFAIP3 polymorphisms (rs2230926, rs5029939, rs10499194, rs6920220, rs582757) were analyzed in the present study. No significant association could be observed between rs2230926, rs5029939, rs6920220, rs582757 and the susceptibility to AIH-1 in Chinese Han population. Compared with wild-type genotype CC at rs10499194, individuals carrying CT genotype had a significantly increased risk for developing AIH-1 (OR = 2.32, 95%CI 1.44-3.74). Under a dominant model, CT/TT carriers have a 140% increased risk of AIH-1 than CC carriers (OR = 2.40, 95%CI 1.50-3.87). The rs10499194 T allele was also found to be significantly associated with AIH-1 risk (OR = 2.41, 95%CI 1.51-3.82). In addition, higher serum ALT, AST levels and more common cirrhosis were observed in AIH-1 patients with T allele (CT/TT) than those with CC genotype. In conclusion, TNFAIP3 rs10499194 T allele and CT genotype were associated with an increased risk for AIH-1, suggesting rs10499194 polymorphism as a candidate of susceptibility locus to AIH-1.